1987
DOI: 10.2307/1590782
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Disease Susceptibility and Subclass-Specific Antibody Response in SC and FP Chickens Experimentally Inoculated with Eimeria tenella, E. acervulina, or E. maxima

Abstract: Susceptibility to disease and the subclass-specific antibody response to Eimeria tenella, E. acervulina, and E. maxima were compared in two inbred strains of chickens, FP (B15B21) and SC (B2B2). FP strain was more susceptible to coccidiosis than SC chickens based on oocyst production, lesion score, and clinical signs. FP chickens infected with E. tenella had more severe cecal lesions and a significantly lower hematocrit level than SC chickens. FP chickens infected with E. acervulina excreted five times as many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 17 publications
3
48
0
1
Order By: Relevance
“…These results suggested that fish oil and corn oil decreased the mortality ratio of chickens infected with E. tenella through increasing E. tenella antigen-bindingspecific sIgA levels. A previous study has suggested that two different strains of chickens infected with E. tenella produced higher levels of serum-specific IgG (Lillehoj & Ruff, 1986). Diets without supplemental oils had higher levels of IgG (Table 5), and this result could have contributed to the lower mortality of chickens infected with E. tenella.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These results suggested that fish oil and corn oil decreased the mortality ratio of chickens infected with E. tenella through increasing E. tenella antigen-bindingspecific sIgA levels. A previous study has suggested that two different strains of chickens infected with E. tenella produced higher levels of serum-specific IgG (Lillehoj & Ruff, 1986). Diets without supplemental oils had higher levels of IgG (Table 5), and this result could have contributed to the lower mortality of chickens infected with E. tenella.…”
Section: Discussionmentioning
confidence: 81%
“…The supernatants were determined at 478 nm. A spun micro-haematocrit was prepared in four replicates for each sample for measuring the PCV (Lillehoj & Ruff, 1986;Bryner et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Isotypes of anti-coccidia antibodies in both the circulation and mucosal secretions have been studied (Rose et al, 1984a;Trees et al, 1985;Lillehoj, 1987b;Hughes et al, 1989). Serum IgM peaked 13 to 17 dpi of E. tenella (Trees et al, 1985) and at 10 dpi of E. nieschulzi infection (Rose et al, 1984a).…”
Section: Systemic Responses To Coccidiamentioning
confidence: 99%
“…However, antibody titers in serum and intestine do not correlate with the level of protection after oral infection with coccidia (Lillehoj and Ruff, 1987). Three isotypes of antibodies are recognized in birds, IgM, IgA and IgY, the latter being considered the ortholog of the mammalian IgG (Leslie and Clem, 1969), even though the cDNA encoding the IgY heavy chain shows similarity to mammalian IgE (Parvari et al, 1988).…”
Section: Innate and Acquired Immune Responses To Eimeriamentioning
confidence: 99%
“…The role of parasite-specific antibodies both in serum and mucosal secretions has been extensively studies in coccidiosis (Lillehoj and Ruff, 1987). In general, antibodies are hallmark of host immune response to Eimeria parasites, but are not involved in protection against coccidiosis .…”
Section: Innate and Acquired Immune Responses To Eimeriamentioning
confidence: 99%